HUBUNGAN ANTARA KONSENTRASI KLOROFIL-A DENGAN TINGKAT PRODUKTIVITAS PRIMER MENGGUNAKAN CITRA SATELIT LANDSAT-8 - Mulkan Nuzapril; Setyo Budi Susilo; James P. Panjaitan (Jurnal Teknologi Perikanan dan Kelautan, 2017)
Chlorophyll-a is a phytoplankton pigment involved in photosynthesis. Chlorophyll-a concentration detection through satellite orbiting can only be infered the concentration of chlorophyll-a at sea surface and could not estimate the sea primary productivity. Sea Primary productivity may last up to a depth of compensation or the depth at which the intensity of light stayed at least 1% of sea surface light intensity. However, the aim of this study is tofind out the relationships between the concentration of chlorophyll-a and primary productivity so that the concentration of chlorophyll-a could be used to predict primary productivity. The linear regression equation have been applied to construct model explaing relationship between the chlorophyll-a concentration and sea primary productivity. The equation explaing on chlorophyll-a concentrations with primary productivity is PP = 22.746 + 95.536Keu (RÂ²) = 0.66 where PP is the sea primary productivity, Keu is the average of chlorophyll-a concentration throughout the water column. The results of these equations can be applied to satellite imagery so that it can assist in monitoring water quality conditions.